Diastolic index as a short-term prognostic factor in heart failure with preserved ejection fraction. Issue 2 (17th December 2020) - Hoshida, Shiro; Hikoso, Shungo; Shinoda, Yukinori; Tachibana, Koichi; Minamisaka, Tomoko; Tamaki, Shunsuke; Yano, Masamichi; Hayashi, Takaharu; Nakagawa, Akito; Nakagawa, Yusuke; Yamada, Takahisa; Yasumura, Yoshio; et al.
Abstract : Objective: During follow-up time, the value of prognostic factors may change, especially in the elderly patients, and the altered extent may affect the prognosis. We aimed to clarify the significance of the ratio of diastolic elastance (Ed) to arterial elastance (Ea), (Ed/Ea=(E/e')/(0.9×systolic blood pressure)), an afterload-integrated diastolic index, in relation to follow-up periods and other laboratory factors, on the prognosis of elderly patients with heart failure with preserved ejection fraction (HFpEF). Methods: We studied 552 HFpEF patients hospitalised for acute decompensated heart failure (men/women: 255/297). Blood testing and transthoracic echocardiography were performed before discharge. The primary endpoint was all-cause mortality. Results: During a median follow-up of 508 days, 88 patients (men/women: 39/49) had all-cause mortality. During the first year after discharge, Ed/Ea (p=0.045) was an independent prognostic factor in association with albumin (p<0.001) and N-terminal pro-brain natriuretic peptide (NT-proBNP, p=0.005) levels after adjusting for age and sex in the multivariate Cox hazard analysis. However, at 1 to 3 years after discharge, no other significant prognostic factors, except for albumin level (p=0.046), were detected. In the subgroup analysis, albumin, but not NT-proBNP level, showed a significant interaction with Ed/Ea for prognosis (p=0.047). Conclusion: The prognostic significance of a haemodynamic parameter such as Ed/Ea may be valid only during a short-term period, but that of albumin was persisting during the entire follow-up period in the elderly patients. The clinical significance of prognostic factors in HFpEF patients may differ according to the follow-up period.